2007
DOI: 10.1124/jpet.107.121350
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of Novel Acid Pump Antagonist 7-(4-Fluorobenzyloxy)-2,3-dimethyl-1-{[(1S,2S)-2-methyl cyclopropyl]methyl}-1H-pyrrolo[2,3-d]pyridazine (CS-526)

Abstract: The pharmacological profiles of the novel acid pump antagonist 7-(4-fluorobenzyloxy)-2,3-dimethyl-1-{[(1S,2S)-2-methylcyclopropyl]methyl}-1H-pyrrolo[2,3-d]pyridazine (CS-526) were investigated in terms of hog gastric H ϩ ,K ϩ -ATPase activity, gastric acid secretion, and acute gastroesophageal lesions in comparison with other proton pump inhibitors (PPIs). CS-526 inhibited H ϩ ,K ϩ -ATPase activity in a concentration-dependent manner, with an IC 50 value of 61 nM. The inhibitory effect of CS-526 on H ϩ ,K ϩ -A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Another structure of APA is CS-526. CS-526 has the pyrrolopyridazine structure and is also under development [20].…”
Section: Acid Pump Antagonistsmentioning
confidence: 99%
“…Another structure of APA is CS-526. CS-526 has the pyrrolopyridazine structure and is also under development [20].…”
Section: Acid Pump Antagonistsmentioning
confidence: 99%
“…It was reported that the duration of the inhibitory effect of CS-526 and SCH28080, the aforementioned P-CABs, on gastric acid secretion was shorter than that of PPIs in rats and dogs (Long et al, 1983;Ito et al, 2007), and the effect of TAK-438 was more potent and had a longer duration than that of SCH28080 in rats (Hori et al, 2010). These findings clearly indicate that TAK-438 is a novel P-CAB that exerts a stronger and longer-lasting inhibitory effect on gastric acid secretion than PPIs and the aforementioned P-CABs.…”
Section: Characteristics Of Antisecretory Effect Of Tak-438 801mentioning
confidence: 99%
“…This mechanism allows rapid inhibition of the pump without the need for acidity at its luminal surface because the pump is blocked in midcycle. Several structural derivatives, e.g., imidazopyridines such as SCH28080 (Wallmark et al, 1987) and 8-[(2,6-dimethylbenzyl)amino]-N-[2-hydroxyethyl]-2,3-dimethylimidazo[1,2-a]pyridine-6-carboxyamide (AZD0865) (Gedda et al, 2007), pyrimidines (Yu et al, 2004), imidazonaphthyridines (Simon et al, 2007), and pyrrolopyridazines such as 7-(4-fluorobenzyloxy)-2,3-dimethyl-1-{[(1S,2S)-2-methylcyclopropyl]methyl}-1H-pyrrolo [2,3-d]pyridazine (CS-526) (Ito et al, 2007), have been evaluated as P-CABs. These compounds have higher pK a values than PPIs and are stable at a low pH.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown the potent and reversible inhibitory properties of CS-526 against porcine H ϩ ,K ϩ -ATPase without a covalent binding formation. The potent gastric acid inhibitory effects and antiulcer efficacies of CS-526 have also been shown, and the efficacies of CS-526 are comparable with those of PPIs such as omeprazole, lansoprazole, and rabeprazole (Ito et al, 2007).…”
mentioning
confidence: 85%
“…The major classes of APAs are imidazopyridine (Wallmark et al, 1987;Kromer et al, 2000;Gedda et al, 2007) and acyl quinoline derivatives (Keeling et al, 1991;Pope et al, 1995;Cheon et al, 2001), and most of these compounds have been shown to inhibit H ϩ ,K ϩ -ATPase in a K ϩ -competitive mechanism without any covalent binding, thereby initiating reversible inhibition of H ϩ ,K ϩ -ATPase activities. CS-526 is a novel acid suppressant that is different from PPIs and the aforementioned APAs in that its chemical structure includes a pyrrolopyridazine structure (Ito et al, 2007). We have shown the potent and reversible inhibitory properties of CS-526 against porcine H ϩ ,K ϩ -ATPase without a covalent binding formation.…”
mentioning
confidence: 91%